PENGIRIMAN TEXT MELALUI GELOMBANG FM BERBASIS ARDUINO UNO - HERLAMBANG SYAH SYAH PRIO (Jurnal Teknik, 2018)
There are many devices that can be used to communicate, where communication is information that can be conveyed in the form of data, news or messages in the form of symbols / signs, writing, pictures, or sounds. This study aims to create an alternative device by utilizing FM radio waves, the text sent by FM Transmitter will be received and processed into text and displayed on the LCD on the side of the receiver. As input is used Keyboard PS / 2, Arduino Uno with ATMega328P Chip IC to process data, FM Transmitter as a signal sender ,FM Receiver and LCD to receive and display text. The results show that text can be sent and received well when in and outside the room. Outdoor text can be sent and received well within a distance of ≤35 meters with room temperature of 27 degree Celcius, and in the room text can be sent and received well within a distance of ≤37 meters with room temperature of 25 degree Celsius. Temperature can affect the quality of the signal sent and received by the FM radio, so that outside the text can be sent and received well within a distance of ≤26 meters with 61 degree Celsius temperature.